Her2 overexpression is a rare event in anorectal melanoma - Helmke, Burkhard Maria; Zahel, Tina; Breinig, Marco; Schirmacher, Peter; Aulmann, Sebastian; Kern, Michael A. (Melanoma research, 2010)
Anorectal melanomas (AMs) are very rare and highly malignant tumors that are often diagnosed in advanced stages. After the differentiation between cutaneous melanoma (CM) and AM on the molecular level based on the presence of BRAF mutations, further modes of differentiation opened up, such as the recently discovered immunohistologically relevant protein deleted in malignant brain tumors 1 (DMBT1). Over the past several years, increasingly specific therapies have been developed on the basis of new therapy principles. Tyrosin kinase receptors such as Her2 and EGFR have been awarded a large role in this context. The goal of this study was to examine AMs for a possible expression or overexpression of these markers. Expression analyses of Her2 and EGFR were performed immunohistologically on 25 primary AMs. An overexpression of Her2 (score: 3+) was found in one AM from a 68-year-old female patient among these samples. In contrast, EGFR expression was not found in any of the AMs. The results presented here show that isolated cases of AM may benefit from an additive Her2-directed therapy, as the overexpression of Her2 was found in one of our AM patients.
Gesehen am 19.04.2023